Foods to institutional market of school meals: a study based on publics calls (Research, Society and Development, 2022)
The objective is making to analyze the profile of foods of farming family, through the public calls to the national school feeding program. Method: was aplicate a transverse quantitative and descritive analyze of public calls, available in sites of public accounts and sites of municipalities in the state of pará. The study happened the online way during august 2019 to january 2020. Although was realize 34 downlods of public calls of 24 counties of Metropolitan region of Belém, year of 2017, 2018 and 2019. Results: after analyze the food more solicitated was a cabbage. In group of fruits and pulp fruits the points more frequent are guava, acerola, cupuaçu, passion fruit and açai. Besides in group of vegetables highlight cabbage, pumpkin, cheiro verde and cariru. The macaxeira and sweet potato are highlight in group of cereal, chestnut, tubercle and roots. Conclusion: thus, is possible say that the foods more solicited can characterized like of vegetables origin, in natura and minimally processed, what promove security food and nutritional to students, furthermore encourage a farming family.